Accounting : (Nelson Austrlia Pty Limited, 2007)
ACCOUNTING: INFORMATION FOR DECISIONS, 2ed. is proud to define excellence in its approach to Financial Accounting. Clearly illustrating that accounting is the language of business, all students will be able to drive excellence in their own careers when they start with this strong foundation. This innovative approach continues to provide direction to students who choose accounting careers, and to those who progress through their careers as business managers.